Formation of legislation on pension insurance in France, Great Britain, and Russia. a retrospective Inglés (2021)
The relevance of the study is due to the crisis of modern pension insurance systems and the need to change the paradigm of pension legislation development. The purpose of the study is to identify the features of the formation of legislation on pension insurance in several countries (France, Great Britain, and Russia) at the initial stage of development (before 1914). The novelty is expressed both in the formulation of the problem and in the research methodology (the choice of countries and the period of research, the justification for the use of methods: dialectics, analysis, synthesis, system-structural, sociological, statistical, historical-legal, comparative-legal, formal-legal). The result of the study was the conclusions about the historical conditionality of the peculiarities of the formation of legislation on pension insurance in a particular country. There was early legalization of both voluntary and compulsory pension insurance in France. There was no legislation on pension insurance in the UK during the period under review, despite the early development of relevant institutions in the framework of workshops, guilds, and later in the framework of trade unions and “friendly societies”. In Russia, due to the agrarian nature of the economy, pension insurance did not develop within the framework of workshops and guilds; there were no laws on insurance in case of old age by 1914, while the risks of disability and loss of the breadwinner were regulated by law